â€œ Suatu Tinjauan Terhadap Penerimaan Pajak Bumi Dan Bangunan (PBB) (Studi Kasus Desa Rambah Tengah Hilir Kecamatan Rambah Kabupaten Rokan Hulu)â€ - SARI, EBI KURNIA (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2015)
This study aims to determine how the implementation of an increase in the acceptance of Land and Building Tax (PBB ) and obstacles in achieving the target of tax revenue in the village of Rambah Tengah Hilir District Rambah of Rokan Hulu. Objects in this study is a whole community Taxpayers Village Rambah Tengah Hilir as a sample selected by using random proportional to the number of samples taken by the formula Slovin as many as 88 people. The research data were collected using a questionnaire with Likert scale. Data were analyzed by using quantitative descriptive analysis technique that shows a picture of the results on the level of achievement of the respondents ( TCR ) for each of the questions given . The results of this study showed that the implementation of the increase in land and building tax revenues respondents tended to assess the implementation of the input ( input ) in the category Good Enough. This is indicated by the value of the TCR to the assessment of tax payers against officers amounted to 64,38 % with the classification level of achievement of respondents in the criteria Less Good. While Throghput ( process ) of 64,85 % voting classification Achievement Level Respondents in Less Good criteria , and the final output ( output ) targets and the realization of the TCR value of 51,18 % with a classification level of achievement of respondents in the criteria not Good . To achieve the target of land and building tax revenues remains to be done is to collect data on taxpayer, implementing active collection gradually based on STPs , improve the quality of service to the community , make an appeal letter taxpayer to immediately fulfill its obligation to pay the tax on land and buildings ( PBB ).